Indicators used in setting the countercyclical capital buffer - Simo Kalatie; Helinä Laakkonen; Eero Tölö (Bank of Finland, 2015)
According to EU legislation, the national authorities should use the principle of 'guided discretion' in setting the countercyclical capital buffer (CCB), which increases banks' resilience against systemic risk associated with periods of excessive credit growth. This means that the decision should be based on signals from a pre-determined set of early warning indicators, but that there should also be room for discretion, as there is always uncertainty associated with the use of early warning indicators. The European Systemic Risk Board (ESRB) recommends that the authorities use the deviation of the credit-to-GDP ratio from its long term trend value (credit-to-GDP gap) as the primary indicator in setting the CCB. In addition, designated authorities should use in their decision making indicators that measure private sector credit developments and debt burden, overvaluation of property prices, external imbalances, mispricing of risk, and strength of bank balance sheets. Based on an empirical analysis of data on EU countries and a large assortment of potential indicators, we propose a set of suitable early warning indicators for each of these categories.
URN:NBN:fi:bof-201503241123
Keywords: G01; G28; 330